The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1085/jgp.84.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Phycomyces: detailed analysis of the anemogeotropic response.

Abstract: Stage I Vb sporangiophores of Phycomyces grow into the windthe anemotropic response-and away from gravity-the geotropic response . A procedure has been designed to measure the equilibrium bend angle that results when the two stimuli are given simultaneously over a long period of time . This angle will be referred to as the anemogeotropic equilibrium angle. This measurement of a sensory response is analogous to the photogeotropic equilibrium angle in which the variable stimulus is light instead of wind . We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Since the magnitude of wall stress is a function of cell turgor pressure, values for cell turgor and for the factors which control turgor are needed for quantitative models of the mechanics of sporangiophore growth. Moreover, it has been argued that the avoidance and wind responses of Phycomyces are controlled by the concentration of water vapor surrounding the sporangiophore (Gyure et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Since the magnitude of wall stress is a function of cell turgor pressure, values for cell turgor and for the factors which control turgor are needed for quantitative models of the mechanics of sporangiophore growth. Moreover, it has been argued that the avoidance and wind responses of Phycomyces are controlled by the concentration of water vapor surrounding the sporangiophore (Gyure et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Interlaced throughout this literature are references to effects of water vapor, long regarded as the avoidance gas by Gamow and his co-workers (e.g., Johnson and Gamow, 1971;Gamow and Bottger, 1982b;Pellegrino et al, 1983;Gyure et al, 1984). As noted above, the idea that sporangiophores avoid water goes back to Wortmann (1881), who obtained different results with wet and dry pasteboard.…”
Section: Effects Of Water Vapormentioning
confidence: 99%
“…Materials that actively absorb water, such as NaOH, KOH, or plaster saturated with CaCl2, did not attract sporangiophores (Elfving, 1916(Elfving, -1917. Attempts to generate growth responses to step-changes in relative humidity have consistently failed (Cohen et al, 1975(Cohen et al, , 1979Gyure et al, 1984). Gyure et al (1984) found that sporangiophores grew more steeply (over periods of several hours) into wet winds then dry winds, but the relevance of this to avoidance is not clear.…”
Section: Effects Of Water Vapormentioning
confidence: 99%
“…This apparent contradiction might be resolved if it could be shown that a humid wind caused an overall softening of the sporangiophore's cell wall which may have directly enhanced bending. In support of this hypothesis, Gyure et al (5) reported that after several hours of growth in a high humidity wind, the cell wall begins to weaken under the weight of the sporangiophore's head, and the head begins to droop. The data obtained in the present investigation also support the hypothesis that the cell wall becomes softer when exposed to humid wind.…”
mentioning
confidence: 94%
“…Recent studies using a humidified wind tunnel have shown that as the humidity of the wind is increased, the sporangiophore shows a quantitative increase in its equilibrium bend angle (5). This observation argues against Pellegrino's (9, 10) mass transfer model.…”
mentioning
confidence: 95%